Gerenciamento de resíduos de serviços de saúde : uma avaliação em drogarias e farmácias de manipulação - Moro, Leila Dal (2013)
This paper discusses the problem of waste from health services (RSS) generated in drugstores and pharmacies in Marau, Brazil, aiming at the minimization of environmental impacts caused by the materials used in healthcare improperly discarded in the environment such as services , for example, syringes and needles. We seek to provide guidance to the management and proper disposal and management of the same, advising on what can be reused, recycled or treated and what should be referred to final destination safe, avoiding risks to the population. One of the main causes of the progressive growth of the residues of these establishments is the continued and increasing use of disposables, which can, with greater or lesser intensity, causing contamination of water quality and cause pollution. The overall objective of the study was to identify the appropriate process management to RSS drugstores and pharmacies in the city under study, with respect to legislation. The information was collected in the form of interviews and completing a questionnaire. Was observed as search results, the diagnosis of the current waste management system of health services in drug stores and pharmacies in the city. The results show that most companies generate about 15 liters, that most of these wastes are classified as expired medications. Thus, a proposal for such waste management plan and the implementation and monitoring of PGRSS was prepared, assisting in the resolution of environmental, health and social problems caused by these wastes